Global perspectives on CYP2D6 associations with primaquine metabolism and Plasmodium vivax radical cure - Olvany, Jasmine M.; Williams, Scott M.; Zimmerman, Peter A. (Frontiers in Pharmacology, 2022)
Clinical trial and individual patient treatment outcomes have produced accumulating evidence that effective primaquine (PQ) treatment of Plasmodium vivax and P. ovale liver stage hypnozoites is associated with genetic variation in the human cytochrome P450 gene, CYP2D6. Successful PQ treatment of individual and population-wide infections by the Plasmodium species that generate these dormant liver stage forms is likely to be necessary to reach elimination of malaria caused by these parasites globally. Optimizing safe and effective PQ treatment will require coordination of efforts between the malaria and pharmacogenomics research communities.